The roles of autophagy and thyroid hormone in the pathogenesis and treatment of NAFLD - Zhou, Jin (Hepatoma Res, 2021)
Non-alcoholic fatty liver disease (NAFLD) is the most prevalent chronic liver disorder worldwide. It comprises simple steatosis and non-alcoholic steatohepatitis (NASH), which can further progress to cirrhosis and hepatocellular carcinoma. The pathogenesis of NAFLD involves genetic, environmental, and endocrine factors, and several molecular mechanisms have been identified. In this review, we discuss the recent findings on the role of autophagy, in particular lipophagy and mitophagy, in hepatic lipid oxidation. We discuss the pre-clinical and clinical evidence suggesting that impairment of autophagy exacerbates NAFLD progression and restoration of autophagy exerts beneficial effects on NAFLD. We discuss how thyroid hormone (TH) simultaneously regulates lipophagy, mitophagy, and mitochondrial biogenesis to increase β-oxidation of fatty acids and reduce steatosis in the liver. Lastly, we discuss the recent clinical progress in using TH or thyromimetics in treating NAFLD/NASH.